A STUDY ON THE RELATIONSHIP AMONG ZOOPLANKTONS AND DIFFERENT ABIOTIC FACTORS AT BARDA BANDHARAN WETLAND, KODINAR - Dave, Mehul P; Chavda, Nikul B. (International Journal of Research -GRANTHAALAYAH, 2018)
Wetland ecosystems are among the most productive ecosystems in the biosphere. Wetland ecosystem supports the growth of Biodiversity. Hydrology of wetland water gives idea about physical and chemical properties of water and their relationship with ecosystem Biodiversity. In present study we investigate relation between Abiotic factors on Zooplankton Diversity. Phytoplankton is integral components of freshwater wetlands, which significantly contribute towards succession and dynamics of zooplankton and fish. In preset study we have investigated Zooplankton Diversity fluctuation with changing Abiotic factors during Pre, Middle and post winter during 2016-17 of Barda Bandharan (Temporary wetland) near Barda Village, Kodinar, Gujarat.